The Effect Of Work Environment and Organisational Culture On Work Productivity Through Job Satisfaction In Employees Of The Automotive Component Industrial Area in Karawang - Sabil Sabil; Lukman Hakim; Amin Setio Lestiningsih; Dwiyatmoko Puji Widodo (Dinasti International Journal of Education Management And Social Science, 2024)
Increasing employee work productivity is a major challenge in facing competition in the automotive industry. This study aims to investigate the effect of work environment and organizational culture on work productivity through job satisfaction among employees of the Karawang automotive industrial park. The sample population taken from automotive component employees taken was 190. The research method used was quantitative, with data collection conducted through questionnaires.  Data analysis was carried out using Partial Least Squares (PLS) 3.0 as a statistical analysis tool to test the relationship between variables. The results showed that work environment and organisational culture have a significant influence on employee job satisfaction. In addition, work environment, organisational culture, job satisfaction have no effect on work productivity and the effect of organisational culture and work environment on work productivity through job satisfaction has no effect. The findings make an important contribution to practitioners and policy makers in the automotive components industry, highlighting the importance of creating a conducive work environment and organisational culture to create job satisfaction. This study also provides insights for further research into the factors that influence work productivity in the automotive component industry sector.   Abstract: Increasing employee work productivity is a major challenge in facing competition in the automotive industry. This study aims to investigate the effect of work environment and organizational culture on work productivity through job satisfaction among employees of the Karawang automotive industrial park. The sample population taken from automotive component employees taken was 190. The research method used was quantitative, with data collection conducted through questionnaires.  Data analysis was carried out using Partial Least Squares (PLS) 3.0 as a statistical analysis tool to test the relationship between variables. The results showed that work environment and organisational culture have a significant influence on employee job satisfaction. In addition, work environment, organisational culture, job satisfaction have no effect on work productivity and the effect of organisational culture and work environment on work productivity through job satisfaction has no effect. The findings make an important contribution to practitioners and policy makers in the automotive components industry, highlighting the importance of creating a conducive work environment and organisational culture to create job satisfaction. This study also provides insights for further research into the factors that influence work productivity in the automotive component industry sector.